Fathers help to improve breastfeeding practice : can Indonesian fathers provide the same help ? - Februhartanty, Judhiastuty; Muslimatun, Siti; Septiari, Mariyasari (Universa Medicina, 2007)
The objectives of this paper are i) to explore factors influencing practices of timely breastfeeding initiation and exclusive breastfeeding with special attention on factors related to the roles of father; and ii) to elaborate possible factors influencing fatherâs roles in breastfeeding based on literatures from the developed world. Studies conclude that fatherâs roles in supporting breastfeeding include participation in decision on infant feeding mode, involvement in child care taking and household tasks, as well as being the protector and the family provider. They also explore that the quality of couple relationship, parental knowledge and attitudes, characteristics of parental function, and the burden on the family economy are barriers which discourage fathers from being supportive towards breastfeeding. Indonesian fathers may influence breastfeeding in the same way and also experience similar barriers. However, due to different exposure to norms, beliefs, and cultures, a specific study on this matter is very relevant to be carried out in Indonesia prior to any breastfeeding promotion targeted to fathers.